Intercalation and Structural Reconstruction of Ca/Al Layered Double Hydroxides - Abriyanto, Danang; Juleanti, Novie; Normah, Normah; Lesbani, Aldes (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2024)
The intercalation of of Ca/Al layered double hydroxide (LDH) has been successfully conducted into using several intercalants with different size compounds after termal treatment process to reconstruct structure of Ca/Al LDH. Ca/Al LDH was synthesized by co-precipitation at pH 11 then calcination at various temperatures following with intercalation using water, sodium hydroxide, sodium carbonate and Keggin type of polyoxometalate K4[α-SiW12O40]. Characterization of Ca/Al LDH was carried out by XRD and FTIR analyses. XRD analysis showed that unique diffraction peak of Ca/Al LDH at 10o with interlayer space 4.67 Å. Gradual thermal treatment of Ca/Al LDH was achieved until loss unique diffraction peak at temperature 700 oC to form shrinking layer. Intercalation of water, sodium hydroxide, sodium carbonate, and polyoxometalate to shrink layer of Ca/Al LDH can create formation of well crystalline LDH to reconstruct layer structure with formation of unique diffraction at 10◦. The interlayer distance of Ca/Al LDH was increased after intercalation process. Thus reconstruction structure of LDH was successfully conducted with flexibility of layer.